Asymptotically Well-Posed Boundary-Value Problems - Kengne, E. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
In a domain that is the Cartesian product of an interval and a straight line, we investigate a two-point boundary-value problem for partial differential equations. We establish conditions under which this problem is asymptotically well posed in the class of bounded differentiable functions.